Pengembangan Perkuliahan Kimia Bahan Makanan Menggunakan Pendekatan STSE dan Inkuiri Reflektif untuk Meningkatkan Keterampilan Berpikir Evaluatif dan Pemecahan Masalah. - Sofia, - (IOP Publishing, 2021)
This research aims to develop and test the effectiveness of the Food Chemistry (FC) lecture program using the Science Technology Society and Environment and Reflective Inquiry (STSE-IR) approach which can improve evaluative and problem-solving thinking skills of chemistry pre-service teachers. The mixed-method research with embedded experimental which consists of initial studies, development and implementation and interpretation of data was applied in this study. 26 chemistry teacher candidate students were selected as the research sample. In addition, the research instruments that were used to answer research problems are as follows. 1) 1) How does the teaching and learning program use the STSE-IR approach? 2) How do the students' evaluative thinking skills use the STSE-IR approach. 3) How do Students' problem-solving skills use the STSE-IR approach. 4) How do the response of the Chemistry pre-service teacher to the advantages and limitations of the STSE-IR teaching and learning activities. Data were analyzed both qualitatively and quantitatively. The results of the study show the following results. 1) The design of the KBM lecture program uses the STSE-IR approach that has been tested and is quite effective in improving evaluative thinking skills and problem-solving skills of Chemistry Pre-service teacher students. 2) The FC lecture uses the STSE-IR approach which is developed to more effectively improve the evaluative thinking skills of chemistry pre-service teacher with a percent N-gain value of 77.20. % and significantly different compared to the conceptual approach. 3) The FC lecture program uses the STSE-IR approach which is developed to more effectively improve the solving skills of prospective chemistry pre-service teacher with a percent N-gain value of 81.27% and is significantly different versus conceptual approach. 4) Student responses to the advantages and limitations of FC lectures using the STSE-IR approach are as follows. Lectures are considered fun, they created the relevant material to real life therefore it is easy for students to understand concepts, also increase motivation, attitudes, evaluative thinking skills and problem solving. The limitation of this lecture program is that it requires time and money to implement the technology design that has been designed. Keywords: Food chemistry, evaluative thinking skills, problem solving skills, STSE-IR approach.